The Age of Menarche as Related to Physical Growth of Junior High School Girls in Jakarta - Samsudin, Samsudin (Paediatrica Indonesiana, 1990)
A study on the age of menarche and its relation to physical growth was conducted in 1444 junior high school girls who were selected by means of stratified random sampling from districts in Jakarta. This study revealed that 1276 girls had already menarche at differet ages, 56.4% of them at the age under 13 years with 1.6% at the age 9-10 years. The mean age of menarche was 13.0 ± 1.1 years. The relationship between the age of menarche and physical growth was studied on a subsample of 301 girls consisting of 133 whose age of menarche was the same as the chronological age at the time of study, and 168 who had not yet had menarche. Comparison on physical growth was based on weight, height, MUAC, and triceps skinfold respectively. The study reveal that significant higher values on those indices were observed in girls who had already had menarche as compared to the same age girls who had not yet. The value of difference was higher in younger age group as compared to the older one. Besides that the relatively higher values of weight for height combined with higher values for triceps skinfold indicates the relative overweight in girls with younger age of menarche. This study showed that menarche may occur at less than 13 years if a girl showed faster physical growth and was relatively overweight, altough many other factors of growth and development should also be considered.